Management of an Environmental Education Program in Konawe Regency - Fatima Kadir, Sitti; Ningsih, Ratna; La Fua, Jumarddin; Raehang, Raehang; Obaid, Yahya; Umi Nurlila, Ratna (KnE Social Sciences, 2022)
Classes are taught on the environment at Marga Karya Elementary School. Konawe Regency’s goal was to introduce students to the environment at a young age so that they can develop responsible environmental behavior. This study used a qualitative approach and found that schools have provided a conducive climate through the management of environmental education programs that are used to develop character and environmental care behavior in students. Environmental care behavior has been developed through a series of activities that were curriculum-planned, systematic and involved all school components, including environmental education program preparation, implementation and participation of the school community. The school’s approach can be used to encourage students to have a positive view of environmental management, and thereby want to create a clean, beautiful, healthy and comfortable environment, as well as contribute to future sustainable development. Keywords: environmental education, environmental management, environmental care behavior